I see what you mean: Semantic but not lexical factors modulate image processing in bilingual adults. - Vingron, Naomi; Furlani, Noah; Mendelson, Olivia; Titone, Debra (Memory & Cognition, 2022)
Bilinguals frequently juggle competing representations from their two languages when they interact with their environment (i.e., nonselective activation). As a result, both first (L1) and second language (L2) communication may be impeded when words share orthographic form but not meaning (i.e., interlingual homographs; e.g., CRANE, a machine in English, a skull in French). Similarly, bilinguals' reduced exposure to each known language makes bilingual lexical processing more vulnerable to larger frequency effects. While much is known about processes within the language system, less is known about how the bilingual language system interacts with the visual system, specifically in the context of image processing. We investigated this by testing whether commonly observed semantic (homograph interference) and lexical (frequency) effects extend to a visual word–image matching task. We tested 48 bilinguals, who were asked to determine whether an image corresponded to a written word that was presented immediately beforehand. By modulating the complexity of visual referents and the semantic (Analysis 1) or lexical (Analysis 2) complexity of word cues, we simultaneously burdened the visual and language systems. The results showed that both semantic and lexical factors modulated response accuracy and correct reaction time on the word–image matching task. Crucially, we observed an interaction between the image factor (visual complexity) with the semantic (homograph status) but not the lexical factor (word frequency). We conclude that it is possible for the language and image processing systems to interact, although the extent to which this occurs depends on the degree of linguistic processing involved.